1998
DOI: 10.1002/(sici)1098-1063(1998)8:3<244::aid-hipo7>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Theta oscillations in somata and dendrites of hippocampal pyramidal cells in vivo: Activity-dependent phase-precession of action potentials

Abstract: Theta frequency field oscillation reflects synchronized synaptic potentials that entrain the discharge of neuronal populations within the D100-200 ms range. The cellular-synaptic generation of theta activity in the hippocampus was investigated by intracellular recordings from the somata and dendrites of CA1 pyramidal cells in urethaneanesthetized rats. The recorded neurons were verified by intracellular injection of biocytin. Transition from non-theta to theta state was characterized by a large decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
393
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 497 publications
(432 citation statements)
references
References 84 publications
(182 reference statements)
38
393
1
Order By: Relevance
“…Some of the single cell models assume that precession arises in CA1 (Kamondi et al, 1998;Magee, 2001;Harris et al, 2002;Mehta et al, 2002). Another class of phase precession models explicitly requires a network of neurons.…”
Section: Comparison With Other Modelssupporting
confidence: 76%
See 2 more Smart Citations
“…Some of the single cell models assume that precession arises in CA1 (Kamondi et al, 1998;Magee, 2001;Harris et al, 2002;Mehta et al, 2002). Another class of phase precession models explicitly requires a network of neurons.…”
Section: Comparison With Other Modelssupporting
confidence: 76%
“…To be more specific, hippocampal pyramidal cells exhibit membrane potential oscillations in the theta range, which reflect the electroencephalogram (EEG) theta oscillations of the field potential. Intracellular theta oscillations have amplitudes of up to 10 mV in anesthetized animals (Kamondi, Acsady, Wang, & Buzsáki, 1998;Bland, Konopacki, & Dyck, 2005), and were also observed in behaving animals (Lee, Manns, Sakmann, & Brecht, 2006). The maximum of the somatic membrane potential oscillation corresponds to the minimum of the EEG in the stratum pyramidale (Kamondi et al, 1998), which is defined as 0 degree in accordance with Csicsvari, Hirase, Czurkó, Mamiya, and Buzsáki (1999) and Buzsáki (2002).…”
Section: Hippocampal Phase Precession Through Mossy Fiber Facilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Perforant path input to distal dendrites of the CA1 and CA3 pyramidal cells and dentate granule cells is believed to produce current dipoles that are responsible for the large amplitude of theta at around the hippocampal fissure (Buzsáki et al, 1983). This latter oscillator is atropine-resistant, but is abolished by urethane anesthesia and lesions of the entorhinal cortex and originates mainly in layers 2/3 of the entorhinal cortex Ylinen et al, 1995b;Kamondi et al, 1998). In support of this hypothesis, many layer 2/3 cells of the entorhinal cortex are phase-locked to the hippocampal theta (Alonso and Garcia-Austt, 1987b;Chrobak and Buzsáki, 1998b;Alonso and Llinás, 1989), and the theta waveshape reverses around layer 2 of the entorhinal cortex (Alonso and Garcia-Austt, 1987a;Mitchell and Ranck, 1980).…”
Section: Slow (<1 Hz) Rhythms-mirceamentioning
confidence: 99%
“…In entorhinal cortex stellate cells, experiments have shown that the oscillations result from an interaction of the persistent sodium current I NaP and the hyperpolarization activated inward current I h [6,13,14]. Recordings from hippocampal CA1 pyramidal neurons have also demonstrated ongoing oscillations in the dendrites that include repetitive dendritic spikes, presumably involving Ca 2+ currents [15].…”
Section: Introductionmentioning
confidence: 99%